The liver graft before transplantation defining outcome after liver transplantation - Verhelst, Xavier (Academic Press, 2024)
"The Liver Graft Before Transplantation: Defining Outcome After Liver Transplantation provides a comprehensive overview of pretransplant assessment and conditioning of liver grafts to guide the best strategy for successful transplantation and better outcomes for patients. Sections provide an overview of the history and indications for liver transplantations as well as coverage of current practices used in transplantation. Next, donor and liver graft assessment are discussed with specific coverage of diseases that carry a risk of recurrence after liver transplantation, including hepatocellular carcinoma, NASH, primary biliary cholangitis, primary sclerosing cholangitis, and viral hepatitis. Finally, the impact of the use of suboptimal liver grafts and clues to make the right trade-off between benefit and risk are discussed. This is the perfect reference for clinicians who need a comprehensive, clinically relevant overview of pretransplant assessment and conditioning of liver grafts and want to know what to expect in future years"--